Body mass index change and estimated glomerular filtration rate decline in a middle-aged population: health check-based cohort in Japan - Rajiv Saran; Yukari Yamada; Tatsuyoshi Ikenoue; Shingo Fukuma; Jennifer Bragg-Gresham; Edward Norton; Daichi Kohmoto (BMJ Open)
Background Obesity is a growing public health problem worldwide. We evaluated the mediators and association between changes in obesity metrics and renal outcomes in the general population.Methods Using the Japanese nationwide health check-based cohort from April 2011 to March 2019, we selected individuals aged 40–74 years, with a baseline estimated glomerular filtration rate (eGFR) ≥45 mL/min/1.73 m2, whose body mass index (BMI) change was assessed. The primary outcome was combined 30% decline in eGFR, eGFR <15 mL/min/1.73 m2 and end-stage renal disease.Results During 245 147 person-years’ follow-up among 50 604 participants (mean eGFR, 83.7 mL/min/1.73 m2; mean BMI, 24.1 kg/m2), 645 demonstrated eGFR decline (incidence rate 2.6/1000 person-years, 95% CI: 2.4 to 2.8). We observed continued initial changes in BMI for over 6 years and a U-shaped association between BMI change and eGFR decline. Compared with 0% change in BMI, adjusted HRs for changes of −10%, −4%, 4% and 10% were 1.53 (95% CI: 1.15 to 2.04), 1.14 (95% CI: 1.01 to 1.30), 1.16 (95% CI: 1.02 to 1.32) and 1.87 (95% CI: 1.25 to 2.80), respectively. The percentage of excess risk of BMI increase (>4%) mediated by three risk factors (blood pressure, haemoglobin A1c and total cholesterol), was 13.3%.Conclusion In the middle-aged Japanese population, both, increase and decrease in BMI were associated with subsequent eGFR decline. Changes in risk factors mediated a small proportion of the association between BMI increase and eGFR decline. Our findings support the clinical significance of monitoring BMI as a renal risk factor.